Formation of a professional communication culture among future psychologists in higher education institutions as a scientific problem - Pedorenko, Vitalii; Sereda, Nataliia (Impressum, 2024)
The article explores how modern challenges impact mental health and underscores the role of communication culture in the psychology profession. Recent studies on Ukrainian citizens’ mental health reveals a rise in stress levels and growing demand for psychological support, with a particular trust placed in psychologists. The text emphasizes that communication is foundational to psychological practice. It further explores the concept of «communication culture» and «professional communication culture» as essential across various fields. The specifics and structure of the concept of «culture of professional communication» of psychologists are considered. Findings suggest that enhancing communication training in psychology education can improve professional competency and better address the rising mental health needs in society.
Keywords: culture; communication; professional communication culture; future; psychologists